Evaluation of the Response to Ranibizumab Therapy following Bevacizumab Treatment Failure in Eyes with Diabetic Macular Edema - Hanhart, Joel (Case Rep Ophthalmol, 2015)
BACKGROUND/AIMS: Bevacizumab and ranibizumab are routinely used to treat diabetic macular edema (DME). We aim to evaluate the usefulness of switching to ranibizumab therapy following bevacizumab treatment failure in eyes with DME. METHODS: We performed a retrospective analysis of a consecutive group of patients with DME who received ranibizumab injections following the failure of bevacizumab injections. The injections were delivered following a pro re nata protocol every 4–6 weeks. The data collected included demographics, systemic and ophthalmic findings, as well as the central subfield thickness according to spectral-domain OCT. RESULTS: Eight eyes (5 patients) were included in the study. The median number of bevacizumab injections prior to the switch to ranibizumab was 4, and the median number of ranibizumab injections during the study was 2. The mean follow-up period was 541 ± 258 days. The mean central retinal thickness (CRT) (±SEM) was 539 ± 75 μm before the initiation of bevacizumab treatment, and 524 ± 43 μm after the last bevacizumab injection (p = 0.7). It reduced to 325 ± 26 μm following the ranibizumab injections (p = 0.0063). The best-corrected visual acuity (BCVA) improved in 4 eyes and remained stable in 4 eyes following the ranibizumab injections. CONCLUSION: A ranibizumab therapy was effective in reducing the CRT in eyes that failed bevacizumab therapy. A BCVA improvement can also occur in these eyes. Switching between anti-vascular endothelial growth factor compounds may be beneficial in eyes with DME.